KAP Survey On Adverse Drug Reaction Reporting And Risk Management Among Pharmacist, Nurse, Dentist And General Practitioners In Saudi Arabia (Journal of Namibian Studies : History Politics Culture, 2023)
Objective: The study aimed at assessing the KAP on Adverse Drug reaction reporting and risk management among Healthcare Professionals in Saudi Arabia.Methods: A cross-sectional survey study was conducted where Participants were recruited from an online survey via a self-reported questionnaire. The data were captured in Microsoft Excel 2021 and were analyzed using Statistical Package for Social Sciences. To examine the potential differences in the mean KAP score among Dependent Variables (Knowledge, Attitude, Practice on ADR reporting and risk management) and independent variables (Occupation) repeated measures ANOVA was conducted. A p-value below 0.05 was deemed statistically significant.Results: KAP scores of Pharmacists were (1.9032, 3.1935, 3.3226) is higher when compared with Dentists (1.6667, 2.7778, 3.6667) and General Practitioners (1.1111,1.5, 3). The factor interaction of Participants of the different healthcare fields and KAP scores were not significant (F 2.477, p value 0.097, ɳ2 = 6.871).Conclusion: Pharmacists exhibited superior understanding and disposition towards ADR reporting. Hence, it is imperative to enhance awareness and advocate for ADR reporting.